2019
DOI: 10.3892/etm.2019.7902
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑663 participates in myocardial fibrosis through interaction with TGF‑β1

Abstract: MicroRNA-663 (miRNA-663) regulates the expression of transforming growth factor β1 (TGF-β1), which participates in the pathogenesis of myocardial fibrosis. Therefore, microRNA-663 may also serve a role in myocardial fibrosis. The present study aimed to determine whether miRNA-663 participates in myocardial fibrosis via interaction with TGF-β1. In the present study, the expression of miRNA-663 was significantly downregulated, whereas that of TGF-β1 was significantly upregulated in the endomyocardial biopsies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In contrast, miR-10a promotes cardiac fibrosis by increasing the expression levels of α-SMA, collagen-I, and collagen [ 53 ], while miR-155 leads to hyperactivation of pro-fibrotic TGF-β1/Smad3 signaling pathway and the excessive cardiac fibrosis [ 56 ]. Additionally, miR-133 [ 25 ], miR-633 [ 50 ], miR-425 and miR-744 [ 48 ], and miR-22 [ 33 ] can directly target TGF-β1 and reduce its expression level. However, some studies reported that miR-22 could also target TGFβR1 and PTAFR to achieve the anti-fibrotic capacity [ 34 , 35 ], suggesting that miRNAs could regulate the pathway by simultaneously targeting multiple crucial genes.…”
Section: The Functions Of Mirnas In Cardiac Fibrosis-related Signalin...mentioning
confidence: 99%
“…In contrast, miR-10a promotes cardiac fibrosis by increasing the expression levels of α-SMA, collagen-I, and collagen [ 53 ], while miR-155 leads to hyperactivation of pro-fibrotic TGF-β1/Smad3 signaling pathway and the excessive cardiac fibrosis [ 56 ]. Additionally, miR-133 [ 25 ], miR-633 [ 50 ], miR-425 and miR-744 [ 48 ], and miR-22 [ 33 ] can directly target TGF-β1 and reduce its expression level. However, some studies reported that miR-22 could also target TGFβR1 and PTAFR to achieve the anti-fibrotic capacity [ 34 , 35 ], suggesting that miRNAs could regulate the pathway by simultaneously targeting multiple crucial genes.…”
Section: The Functions Of Mirnas In Cardiac Fibrosis-related Signalin...mentioning
confidence: 99%
“…In contrast, over-expression of miR-675 could reverse the TGFβ1-induced remodelling and the proliferation of mouse cardiac fibroblasts by targeting TGFβR1 ( Wang et al, 2019a ). Similarly, there were negative correlation between miRNA-663 and TGF-β1 expression in endomyocardial myocardial biopsies from patients with cardiac fibrosis, while over-expression of miRNA-663 resulted in the decreased expression of the cardiac fibrosis markers plasminogen activator inhibitor-1 (PAI-1) and tissue inhibitor of metalloproteinase-1 (TIMP-1) ( Wu et al, 2019 ). MiR-30c expression is downregulated in the atrial samples from AAC model rats and in the TGF-β1-stimulated RCFs, whereas miR-30c over-expression inhibited TGF-β1-induces proliferation, differentiation, migration, and ECM synthesis in cardiac fibroblasts, by directly targeting TGFβRII ( Xu et al, 2018 ).…”
Section: Regulation Of Tgf-β/smad Signaling Pathway By Ncrnas In Card...mentioning
confidence: 99%